The Kimball Group reader : relentlessly practical tools for data warehousing and business intelligence - Kimball, Ralph; Ross, Margy, 1959-; Becker, Bob, 1954-; Mundy, Joy, 1961-; Thornthwaite, Warren, 1957-; Kimball Group (Indianapolis, IN : Wiley, 2016)
Offers a collection of recommended guidelines for data warehousing and business intelligence. Features articles covering the complete lifecycle of data warehousing, including project planning, requirements gathering, dimensional modeling, ETL, and business intelligence and analytics.
The reader at a glance -- Before you dive in -- Project/program planning -- Requirements definition -- Data architecture -- Dimensional modeling fundamentals -- Dimensional modeling tasks and responsibilities -- Fact table core concepts -- Dimension table core concepts -- More dimension patterns and considerations -- Back room ETL and data quality -- Technical architecture considerations -- Front room business intelligence applications -- Maintenance and growth considerations -- Final thoughts.
Includes bibliographical references (pages [853]-860) and indexes.
Print version record.
Keywords: COMPUTERS -- Database Management -- Data Warehousing; Data warehousing; Business intelligence; Business intelligence; Data warehousing; Electronic books